Biomasa y carbono almacenado en las especies comerciales del bosque de colina baja de la concesión forestal n° 16-LOR-MAY/CON-MAD-2017-024, distrito de Mazán, Loreto. 2021 - Meza Chavez, Zwely Zuymei (2022)
The biomass and the carbon stock in the commercial species of a low-hill forest of the Mazán district, Loreto, Peru, were quantified. The data from the forest census of commercial species of the operative plan (PO) 1 of the felling plot (PC) 6 of the forest concession contract for timber purposes N° 16-LOR-MAY/CON-MAD-2017-024 was evaluated. The results indicate a total biomass of 2 092 812,87 kg and 2379,28 kg/ha, where V. calophylla reports the highest amount of total biomass of 964 884,26 kg and 1096,96 kg/ha and C. racemosa reports the lowest amount of total biomass of 631 802,44 kg and 252,72 kg/ha. The carbon stock is 31 959,42 tC and 12,78 tC/ha. V. calophylla (3643,23 tC and 1,46 tC/ha) and A. brasiliensis (3158,88 tC and 1,26 tC/ha) report the highest stocks; while A. giganteum with 456,78 tC and 0,18 tC/ha and C. racemosa with 315,90 tC and 0,13 tC/ha show the lowest stocks. The diameter classes of 90 cm + (8501,12 tC and 3,40 tC/ha) and 60 cm to 69 cm (7606 tC and 3,04 tC/ha) contain the highest amount of carbon stock; while the diameter classes 50 cm to 59 cm (3967,46 tC and 1,59 tC/ha) and 80 cm to 89 cm (4868,51 tC and 1,95 tC/ha) contain the least amount of carbon stock.